GENESIS KAOLIN DAN REKAYASA PEMANFAATANNYA SEBAGAI BAHAN BAKU KERAMIK (Studi Kasus Pada PT Sugih Alam Anugroho, di Kecamatan Belinyu, Kabupaten Bangka, Propinsi Kepulauan Bangka Belitung) = Genesis of Kaolin and Its ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Kaolin is one of the mining material which is found in Belinyu area. Nowdays at Belinyu District area there is an industry owns by PT Sugih Alam Anugroho which produces kaolin powder. This research was intended to study genesis of kaolin and its benefits for ceramic good. The research area is located at Belinyu Sub District, Bangka District, Bangka-Belitung Province. The activities included field and laboratory works. The field activities were to take samples, strike and dip joint, depth and thickness measurements outcrops. Laboratory activities included physical and chemical properties analysis, XRD analysis, and ceramic making and testing. The result showed that genesis of kaolin was weathering processes for residue kaolin and sedimentation processes for sedimentary kaolin which spread at stream valley area. The best result of ceramic product as ceramicware can be made by mixing of 1 part of kaolin and 3 parts by volume of ball clag.